RECONSTRUCTION OF A REHABILITATION APPROACH FOR VICTIMS OF DRUG ABUSE WITH COMMUNITY-BASED INTERVENTION WITH JUSTICE VALUES - Kevin Krissentanu Winner; Milda Istiqomah; Bambang Sugiri (CV. RADJA PUBLIKA, 2025)
The method of handling victims of drug abuse can be done through community-based rehabilitation with therapy methods using a psychosocial approach. Community-based Social Rehabilitation still faces challenges in its implementation. The purpose of this study is to reconstruct the rehabilitation approach for victims of drug abuse with community-based interventions with justice values in order to provide legal protection to victims of drug abuse and reform the Indonesian narcotics criminal law . The research method used is legal research with a statutory regulatory approach, a comparative approach, and a conceptual approach. Based on the research that has been done, it is known that regulations regarding the rehabilitation of victims of drug abuse with a community-based intervention approach still require synchronization of cooperation between the National Narcotics Agency and Regional Governments. because the implementation of community-based interventions without involving Regional Apparatus Organizations causes suboptimal gradual handling programs for victims of drug abuse. In addition, there is an urgency to carry out reconstruction based on the principle of justice referring to the purpose of rehabilitation as treatment or care for drug addicts, so that addicts can recover from their addiction to narcotics.